2022
DOI: 10.3390/foods11244113
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fermented Milk with Fruit Pulp Modulates the In Vitro Intestinal Microbiota

Abstract: The effect of putative probiotic fermented milk (FM) with buriti pulp (FMB) or passion fruit pulp (FMPF) or without fruit pulp (FMC) on the microbiota of healthy humans was evaluated. FM formulations were administered into a simulator of the human intestinal microbial ecosystem (SHIME®) to evaluate the viability of lactic acid bacteria (LAB), microbiota composition, presence of short-chain fatty acids (SCFA), and ammonium ions. The probiotic LAB viability in FM was affected by the addition of the fruit pulp. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 133 publications
0
7
0
1
Order By: Relevance
“…This log reduction may be attributed to the acid output of dried fruit extracts. Also, the starter bacteria’s presence may be an additional suppression of Rayeb milk spoilage [ 27 ]. It is also an added value to produce new fortified milk products that are acceptable to consumers at suitable prices.…”
Section: Resultsmentioning
confidence: 99%
“…This log reduction may be attributed to the acid output of dried fruit extracts. Also, the starter bacteria’s presence may be an additional suppression of Rayeb milk spoilage [ 27 ]. It is also an added value to produce new fortified milk products that are acceptable to consumers at suitable prices.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated genera by dietary NSMJ56 were Flintibacter, Dielma , and Hespellia followed by Coprobacter, Roseburia, Anaerotignum , and Coprococcus. Flintibacter is known to produce SCFA, such as butyrate and constitutes a component of the beneficial microbiota ( Borgonovi et al, 2022 ). Qiu et al (2022) showed that the relative abundance of Dielma genera was positively correlated with SCFAs production.…”
Section: Discussionmentioning
confidence: 99%
“…A high Firmicutes to Bacteroidetes ratio in intestinal microbiota is a typical alteration in individuals with obesity and related diseases [ 44 , 45 ], since Firmicutes could be more effective in extracting energy, especially from carbohydrates, thereby affecting the energetic metabolism [ 46 ]. Increases in Proteobacteria abundance in the intestine have been commonly found in individuals with obesity [ 46 , 47 , 48 ]. Proteobacteria is among the most abundant intestinal microbiota phyla and includes various pathogenic microorganisms (e.g., Enterobacteriaceae members).…”
Section: The Potential Role Of Intestinal Microbiota In Ncdmentioning
confidence: 99%
“…Berg), juçara ( Euterpe edulis Mart. ), and passion fruit ( Passiflora capsularis L.) are widely cultivated and available in Brazil; they are reported as sources of bioactive components that are capable of modulating the composition and metabolic activity of the intestinal microbiota with local and systemic benefits, including anti-inflammatory and antioxidant activity, better insulin sensitivity, body weight reduction, and effective management of dyslipidemia, besides having evidence of low genotoxic [ 10 , 15 , 33 , 44 , 48 , 54 , 81 , 87 ]. Table 1 summarizes the major bioactive compounds found in peel, seed, and/or pulp of Brazilian native fruits that are being investigated for their ability to modulate intestinal microbiota.…”
Section: Bioactive Compounds In Brazilian Native Fruitsmentioning
confidence: 99%
See 1 more Smart Citation